Schwartz-Jampel Syndrome: a paediatric dentistry approach - Turrioni, Ana Paula Silveira [UNESP]; Sakima, Sarah Ayumi [UNESP]; Giro, Elisa Maria Aparecida [UNESP] (Editora Cubo, 2013)
Schwartz-Jampel syndrome (SJS) is a rare recessive disorder characterized mainly by myotonia. As the clinical signs and symptoms are manifested in the oromaxillofacial region, paediatric dentists may be first choice of parents that seek information and assistance to their children. A female patient diagnosed with SJS was brought to our clinic for dental treatment with main complain of difficulty on oral hygiene and mastication due to tooth crowding. The treatment included preventive measures, extraction of a supernumerary tooth and the maxillary primary second molars. Furthermore, the patient was referred to orthodontic treatment for correction of tooth crowding. When dealing with children with confirmed diagnosis of SSJ, paediatric dentists should be understand the need of planning the dental treatment considering the characteristics and possible complications associated with the syndrome in order to reduce the risks to patients, especially when surgical procedures are necessary.

A síndrome de Schwartz Jampel (SSJ) é uma desordem autossômica recessiva rara, caracterizada principalmente pela miotonia. Desde que alguns dos sinais clínicos e sintomas são manifestados na região oromaxilofacial, o odontopediatra pode ser o primeiro profissional a se deparar com um paciente portador desta síndrome. Um paciente do sexo feminino diagnosticado com SJS procurou a nossa clínica para tratamento dental com queixa principal de dificuldade na realização da higiene oral e mastigação, devido ao mau posicionamento dentário. O tratamento incluiu medidas preventivas, extração de um dente supranumerário e dos segundos molares decíduos e encaminhamento para tratamento ortodôntico. Quando uma criança possui o diagnóstico confirmado para SSJ, o odontopediatra deve ter conhecimento específico para planejar e realizar o tratamento odontológico de forma adequada, considerando as características da síndrome e as possíveis complicações associadas, a fim de reduzir os riscos ao paciente, especialmente quando procedimentos cirúrgicos são necessários.
Síndrome de Schwartz-Jampel: uma abordagem odontopediátrica
Keywords: Supernumerary tooth; Malocclusion; Myotonia; Osteochondrodysplasias; Dente suprenumerário; Má-oclusão; Miotonia; Síndrome de Schwartz-Jampel